Biochemical properties of a novel chitosanase from Bacillus amyloliquefaciens and its use in membrane reactor. (November 2018) - Qin, Zhen; Luo, Sa; Li, Yun; Chen, Qiming; Qiu, Yongjun; Zhao, Liming; Jiang, Lihua; Zhou, Jiachun
Abstract: Chitooligosaccharides are widely used in functional food, medicaments and agriculture. Controllable conversion of chitosan to chitooligosaccharides with desired degree of polymerization (DP) is of great value. Herein, a novel glycoside hydrolase family 46 chitosanase (BaCsn46A) was cloned and expressed from Bacillus amyloliquefaciens. BaCsn46A exhibited good enzymatic properties with high specific activity (1031.2 U/mg) under optimal hydrolysis conditions of pH 6.0 and 50 °C. BaCsn46A is an endo-type chitosanase, which could be utilized to yield abundant chitooligosaccharides. Furthermore, the preparation of high degree of polymerization chitooligosaccharides (DP 5–10) was investigated by BaCsn46A in an enzymatic reactor with a subsequent series of membranes. The maximum concentration of total chitooligosaccharides (DP 2–10) was 28.11 g/L (93.70% yield). The proportion of high degree of polymerization chitooligosaccharides (DP 5–10) occupied 56.17% (w/w) of total chitooligosaccharides. This study provided a cleaner production process for the controllable preparation of chitooligosaccharides with specific degree of polymerization. Graphical abstract: Image 1 Highlights: A high-activity chitosanase from B.amyloliquefaciens (BaCsn46A) was identified. BaCsn46A could be used for controllable producing chitooligosaccharides in membrane reactor. High degree polymerized chitooligosaccharides was accumulated by enzyme-membrane coupling process. This study provided a cleaner production process for controllable producing chitooligosaccharides.